2022
DOI: 10.2166/washdev.2022.041
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of adoption and diffusion of ecological sanitation technology: a review of literature

Abstract: Ecological sanitation (Ecosan) technology was introduced to improve sanitation through the reuse of excreta resources, particularly in developing countries. However, the adoption of Ecosan technology is low which makes its diffusion complex, especially in diverse spatial and socio-cultural contexts. This review of literature aimed to use the innovation theory to identify the issues that make the process of adoption of Ecosan technology complex. A total of 105 published studies were reviewed. Of these, only 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, there were conflicting messages on the use of excreta as resources while emerging Ecosan technology in similar communities. In these areas, study findings on the adoption of Ecosan remain inconsistent [ 6 ]. Some studies [ 18 , 26 ] show that people have fully adopted Ecosan and wide use, while other studies [ 17 , 20 ] showed partial Ecosan adoption either as a sanitation option or an agricultural option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were conflicting messages on the use of excreta as resources while emerging Ecosan technology in similar communities. In these areas, study findings on the adoption of Ecosan remain inconsistent [ 6 ]. Some studies [ 18 , 26 ] show that people have fully adopted Ecosan and wide use, while other studies [ 17 , 20 ] showed partial Ecosan adoption either as a sanitation option or an agricultural option.…”
Section: Discussionmentioning
confidence: 99%
“…The human adaptive behaviour of pathogenic disgust is in the context of prevention and control of diseases and is based on technological and cultural evolution [ 4 ]. Only technological complexities in the adoption of Ecosan were explained in a previous study using Roger’s model [ 6 ]. The adaptive behaviour of Ecosan by-products can be explained by the theory of adaptive excreta disgust of Rozin–Haidt–McCauley (RHM) [ 7 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological sanitation (ecosan) is a transformative method to water and sanitation management, embracing a circular nutrient flow and a "closed-loop-approach" that facilitates the return of excreta nutrients to the soil (Esrey, 2001;. It also embodies a comprehensive and enduring strategy for sanitation, rooted in the principles of pollution prevention, hygienic treatment of human waste, and the utilization of urine and feces as valuable resources in agriculture (Banamwana et al, 2022a). Operating in 84 countries, ecosan has a global impact by reducing health risks, preventing pollution, and enhancing water and nutrient resource managements (Abarghaz et al, 2012;Rieck et al, 2012).…”
Section: Ecological Sanitationmentioning
confidence: 99%
“…Concerns about userfriendliness, especially for large families, impact the willingness to adopt ecosan toilets (Kc et al, 2020). Those challenges affect the diffusion and adaption process of the technology globally (Banamwana et al, 2022a).…”
Section: Ecological Sanitationmentioning
confidence: 99%